Moiré Perovskite Photodetector toward High‐Sensitive Digital Polarization Imaging. Issue 29 (21st May 2021) - Song, Qian; Wang, Yang; Vogelbacher, Florian; Zhan, Yan; Zhu, Danlei; Lan, Yangjie; Fang, Wenzhong; Zhang, Zemin; Jiang, Lang; Song, Yanlin; Li, Mingzhu
Abstract: Perovskite (PVK) photodetectors (PDs) have emerged as highly‐efficient versatile optoelectrical devices due to their highly efficient and simple solution‐processable preparation method. Meanwhile, optical structures offer an efficient and facile strategy to improve the light‐harvesting performance of devices and introduce extra optical activity such as polarization sensitivity. Here, an efficient moiré perovskite photodetector with a stacked dual shallow grating structure is designed and fabricated, and sensitive digital polarization imaging is realized. The moiré PVK presents superior ability in light harvesting through the synergistic effects of feedback reflection, diffraction, and excitation of waveguide modes in the dual grating structure. Additionally, the highly crystalline PVK is fabricated through the imprint lithography process. Consequently, excellent device performance is achieved by taking advantage of highly‐efficient light‐harvesting and the good electrical properties of large grain PVK crystals. The responsivity (R) and detectivity (D*) of the moiré PVK PD are up to 15.62 A W and 5.58 × 10 13 Jones, which are 6.7 and 7.8 times larger than that of the flat perovskite photodetector, respectively. The on/off ratio reaches 2.7 × 10 4 . The nanograting array introduces good polarization sensitivity to the moiré PVK PD achieving a peak‐to‐valley ratio of 1.58. Excellent polarization images are obtained using a 576 pixel sensor array. Abstract : Moiré perovskite structures can realize coupled reflection, grating diffraction, and excitation of waveguide modes, leading to strong light harvesting. In addition, they are polarization‐sensitive. A moiré perovskite photodetector is prepared with stacked dual grating structure by using a low‐cost commercial digital versatile disc, resulting in high responsivity (15.62 A W –1 ), detectivity (5.58 × 10 13 Jones), and excellent digital polarization imaging.